Business Model Design for The Tax Application Service Provider (PJAP) Polibatam Startup Through the Business Model Canvas - Rahmadani, Ana Fadilah; Ulfah, Mutia; Arniati, Arniati; Hasanah, Afriyanti; Anjelina, Anjelina; Kurniawan, Dedi; Lanniari, Rizki (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research focuses on designing a business model for Start-up Penyedia Jasa Aplikasi Perpajakan (PJAP) Polibatam. PJAP Polibatam is a startup that focuses on tax education, creating the first and only educational version of a tax reporting application in Indonesia. As a new business, PJAP Polibatam needs to adapt to compete and operate in the long term. Therefore, this study aims to analyze and design the business model of PJAP Polibatam using the Business Model Canvas (BMC) approach. The research method employed is descriptive qualitative, with data obtained through desk research, market validation, and interviews. Subsequently, SWOT analysis, the Four Action Framework, and Porter's Five Forces analysis are conducted. The startup PJAP Polibatam holds significant potential in supporting tax education in Indonesia. With a strong vision and mission, as well as support from relevant stakeholders, this startup has the opportunity to become a pioneer and leader in providing innovative and effective educational tools for tax learning through its educational version of tax application. Market validation indicates a genuine interest and demand from educational institutions for the educational version of tax application.